Hukum Waris Adat pada Masyarakat Muslim Suku Kaili Perspektif Hukum Waris Islam - Al Jihad, Jundi; Irawan, Deni (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
This article aims to determine the system used in applying inheritance distribution according to the Muslim community of the Kaili Tribe in West Palu District, as well as to analyze the Kaili Tribe's customary inheritance law in inheritance distribution application and to look at the review from the perspective of Islamic inheritance law. This study employs a qualitative approach and data collection through field research, specifically using primary data resulting from interviews or observations and secondary data in the form of citations, journals, papers, theses, articles, and literature relating to related issues, with the goal of underpinning the theoretical foundation of writing this article. According to the findings of this study, the majority of inheritance distribution to Muslim communities in West Palu District is done by deliberation and consensus using customary inheritance law. Meanwhile, asset distribution is mandated and must occur before or after the testator's death. This is directly related to Islamic inheritance law, which requires inheritance to be distributed to heirs. The determination of heirs in Kaili customary law is still being reviewed from a kinship standpoint. Children, parents, mawali (posambei), widows or widowers who have lived the longest are the primary heirs. This is antithetical to Islamic law's determination of heir distribution.